Internalisasi dan Aktualisasi Nilai Kesantunan Berbahasa Melalui Kegiatan Ekstrakurikuler Kesenian Tradisional Syarafal Anam pada Siswa MIN 1 Bengkulu Tengah - Utame Nensi, Anita (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
This study discusses the internalization and actualization of language politeness values through syarafal anam traditional arts extracurricular activities at MIN 1 Bengkulu Tengah students. The goal to be achieved is to find out how to internalize and actualize the value of politeness in language to students at MIN 1 Bengkulu Tengah through extracurricular activities of traditional neural anamism art. This research is a qualitative research, the data analyzed in this study are data from interviews and direct observations regarding the values of politeness in the language identified and internalized in the extracurricular activities of traditional neural anam art, as well as the value of language politeness which is actualized in the daily behavior of students at MIN 1 Bengkulu. center is based on Leech's (1993) language politeness principle. The results showed that the principles of politeness identified in the extracurricular activities of traditional neural anam art at MIN 1 Bengkulu Tengah are the maxim of wisdom, maxim of generosity, maxim of praise, maxim of humility and maxim of agreement. The process of internalizing the value of language politeness in students is carried out through habituation and exemplary behavior from both the teacher and the students themselves. The values of politeness in language which are actualized in students' daily behavior are 6 maxims, namely the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement and the maxim of sympathy.